Biomechanical optimization of the magnesium alloy bionic cannulated screw for stabilizing femoral neck fractures: a finite element analysis - Cui, Yunwei; Ding, Kai; Lv, Hongzhi; Cheng, Xiaodong; Fan, Zixi; Sun, Dacheng; Zhang, Yifan; Chen, Wei; Zhang, Yingze (Frontiers in Bioengineering and Biotechnology, 2024)
Purposes The magnesium alloy bionic cannulated screw (MABCS) was designed in a previous study promoting cortical–cancellous biphasic healing of femoral neck fractures. The main purpose was to analyze the bore diameters that satisfy the torsion standards and further analyze the optimal pore and implantation direction for stabilizing femoral neck fractures. Methods The MABCS design with bionic holes with a screw diameter of less than 20% met the torsion standard for metal screws. The MABCS was utilized to repair the femoral neck fracture via Abaqus 6.14 software, which simulated the various stages of fracture healing to identify the optimal biomechanical environment for bionic hole size (5%, 10%, 15%, and 20%) and implantation direction (0°, 45°, 90°, and 135°). Results The stress distribution of the MABCS fracture fixation model is significantly improved with an implantation orientation of 90°. The MABCS with a bionic hole and a screw diameter of 10% provides optimal stress distribution compared with the bionic cannulated screw with diameters of 5%, 15%, and 20%. In addition, the cannulated screw fixation model with a 10% bionic hole size has optimal bone stress distribution and better internal fixation than the MABCS fixation models with 5%, 15%, and 20% screw diameters. Conclusion In summary, the MABCS with 10% screw diameter bionic holes has favorable biomechanical characteristics for stabilizing femoral neck fractures. This study provides a biomechanical foundation for further optimization of the bionic cannulated screw.